Malay Reservations Enactment: protection of Malay rights to hold land in Malaysia / Jamilah Abdul Rauf - Abdul Rauf, Jamilah (Faculty of Law, 1987)
The purpose of this study is to analyse the effects of the enforcement of the Malay Reservations Enactment to the Malays. The Malay Reservations Enactment prohibits the Malays from dealing their lands with non-Malays. This prohibition leads to the Malays, who are lD8inly farmers and fishermen, charging their lands to rich Malays or their institutions. whenever in difficulties financially. The rate of interest is very high as there are very fiew rich Malays or Malay Institution .,ho can lend their money. Many lands have been transferred to these well-to-do Malays, thus showing that the MR laws have helped in keeping the ownership of the lands in hands of the Malays, but not the poor Malays. In the rural MR areas, the Malays live below the poverty line. Lands have not been developed due to lack of capital, rich can only be obtain by borrowing from the rich or other institutions. Thus, the government have initiated several projects to promote development and improve credit facilities.